(untitled) (Dermatology Reports, 2021)
Pemphigus is a group of rare, lifethreatening bullous autoimmune diseases that affect the skin and mucous membranes and are associated with high morbidity and morbidity. HLA class II genes, particularly HLA-DRB1 and HLA-DQB1, play roles in pemphigus. The aim of this paper is to investigate the susceptibility of HLA class II DRB1 and DQB1 alleles in Vietnamese patients with pemphigus vulgaris (PV) or pemphigus foliaceus (PF). The study enrolled 31 participants (22 with PV, 9 with PF) with diagnoses confirmed by clinical manifestations, histopathology, and direct immunofluorescence from November 2019 to June 2020. The HLA polymorphisms were determined by Sanger sequencing. The HLA-DRB1 and HLA-DQB1 profiles of the 101 healthy individuals in the control group have been published previously. The frequencies of HLA-DRB1*14, DRB1*13:07, DRB1*04:04, DRB1*03:02, DQB1*02:02, and DQB1*05:03 were significantly higher, whereas those of DRB1*09:01, DRB1*12:02, DQB1*03:03, DQB1*05:01, and DQB1*06:01 were significantly lower, in the PV group than in the controls. The frequencies of DRB1*14:54, DRB1*13:07, and HLA-DQB1*03:02 were significantly higher in the PF group than in the controls. Alleles HLA-DRB1*14:54, DRB1*14:04, DRB1*14:03, DRB1*14:01, DRB1*14:12, DRB1*13:07, DRB1*04:04, DRB1*03:02, DQB1*02:02, and DQB1*05:03 were associated with an increased risk of PV, whereas alleles DRB1*09:01, DRB1*12:02, DQB1*03:03, DQB1*05:01, and DQB1*06:01 might protect against PV. In PF, DRB1*14:54, DRB1*13:07, and HLA-DQB1*03:02 are promising susceptibility alleles.